FAKTOR–FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PERUSAHAAN MANUFAKTUR DI INDONESIA - Yenny Yenny; Mungniyati Mungniyati (E-Jurnal Akuntansi TSM, 2022)
The objective of this research is to obtain empirical evidence about the effect of leverage, firm size, institutional ownership, managerial ownership, profitability, firm growth and cash on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research uses 71 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 until 2020, with 213 secondary data selected by purposive sampling method and tested using the multiple regression method. The results showed that cash affects earnings management and leverage, firm size, institutional ownership, managerial ownership, profitability and firm growth do not affect earnings management.